Examine your english:a senior course in english grammar and composition - Maison, Margaret M.; Maison, Margaret M. (New Delhi, Orient Blackswan, 1964)
A course in English grammar and composition for students in Indian universities. The book has numerous examples and exercises, and having been designed essentially from an Indian point of view, will enable the Indian student to avoid the usual pitfalls in speech and writing.
Keywords: English language; Linguistics